On the early uses of the word 'gout': novel evidence and a critical assessment of the published literature - F.M. Galassi; L. Ingaliso; V. Papa; R. Lorenzi; E. Percivaldi; E. Varotto (PAGEPress Publications, 2024)
Recognized since antiquity, gout is still a relevant pathology with rising prevalence and incidence. This study aims to assess the reference accuracy in journal articles mentioning the early use of the word 'gout'. Specifically, it investigates whether the term was indeed coined in the 13th century by the Dominican monk Randolphus of Bocking, as widely believed. Several historical sources in their original Latin were consulted to test the hypothesis of literary mentions predating Randolphus of Bocking's description. At the same time, biomedical articles spanning the last two decades were perused using specific keywords in different combinations to determine the accuracy level of references related to the earliest use of the word 'gout'. The results showed that several biomedical publications wrongly ascribed the origin of the word 'gout' to Randolphus of Bocking. Indeed, various texts predate his mention by many years. In particular, gutta, the Latin word used to indicate a host of rheumatological conditions including gout, is recorded as early as the 10th century in a biography dedicated to the martyred nun Saint Wiborada of St. Gall. Written by Swiss monks between AD 960 and 963, this text should be regarded as containing the earliest known adoption of the word. For this reason, scholars should now avoid quoting Randolph of Bocking's description as the first use of the word 'gout' in Western literature.